PEMETAAN PERKEMBANGAN PENELITIAN KARAKTERISTIK PEKERJAAN, MOTIVASI KARYAWAN DAN MANAJEMEN SUMBER DAYA MANUSIA ISLAMI DALAM RANTAI NILAI HALAL: ANALISIS BIBLIOMETRIK BERBASIS SCOPUS - Titin Windiasari; Selamat Riadi; Ahmad Ridho Hidayat; Vegalyra Novantini Samodra (Nusantara Hasana Journal, 2026)
Research on job characteristics within the perspective of Islamic Human Resource Management (IHRM) has gained increasing attention as organizations seek to integrate Islamic values into human resource practices. Nevertheless, comprehensive mapping of the intellectual development of this research area remains limited. This study aims to examine publication trends, knowledge structures, research themes, and future research directions concerning job characteristics in the context of IHRM through a bibliometric approach. The dataset was retrieved from the database using relevant keywords and analyzed with VOSviewer to construct co-occurrence, co-authorship, and citation networks. The findings reveal a substantial growth in publications over the past five years, highlighting major research themes including work motivation, employee engagement, job satisfaction, Islamic work ethics, Islamic leadership, and digital transformation. The analysis further identifies emerging research opportunities related to artificial intelligence integration, halal human resource development, and the incorporation of maqashid sharia into job design. These findings contribute to the enrichment of theoretical development while providing valuable insights for researchers and practitioners in formulating future research agendas and advancing sustainable Islamic Human Resource Management practices.